2007
DOI: 10.1152/ajpregu.00026.2007
|View full text |Cite
|
Sign up to set email alerts
|

Roles of nitric oxide and angiotensin II in the impaired baroreflex gain of pregnancy

Abstract: The present study tested the hypothesis that nitric oxide (NO) contributes to impaired baroreflex gain of pregnancy and that this action is enhanced by angiotensin II. To test these hypotheses, we quantified baroreflex control of heart rate in nonpregnant and pregnant conscious rabbits before and after: 1) blockade of NO synthase (NOS) with Nomega-nitro-L-arginine (20 mg/kg iv); 2) blockade of the angiotensin II AT1 receptor with L-158,809 (5 microg x kg(-1) x min(-1) iv); 3) infusion of angiotensin II (1 ng x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In the pregnant hypertensive group the heart rate decreased compared with normal pregnant rats suggesting that the tachycardia in pregnancy is mediated by nitric oxide, this finding is in agreement with previous report (43,44). One hypothesis is that the progressive increase in heart rate during pregnancy may be a baroreceptor-mediated response to the progressive decrease in blood pressure, however, recently Daubert et al (2007) showed that nitric oxide, either alone or via an interaction with angiotensin II is not responsible for decrease in baroreflex gain during pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…In the pregnant hypertensive group the heart rate decreased compared with normal pregnant rats suggesting that the tachycardia in pregnancy is mediated by nitric oxide, this finding is in agreement with previous report (43,44). One hypothesis is that the progressive increase in heart rate during pregnancy may be a baroreceptor-mediated response to the progressive decrease in blood pressure, however, recently Daubert et al (2007) showed that nitric oxide, either alone or via an interaction with angiotensin II is not responsible for decrease in baroreflex gain during pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Our laboratory and others have ruled out a role for ANG II (6,15,46) and nitric oxide (15). Masilamani and Heesch (41) have implicated a metabolite of progesterone, allopregnanolone, because infusion of this neurosteroid in virgin rats decreases baroreflex gain similarly to that shown during pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, both substances were considered excellent candidates as potential modulators of baroreflex function during pregnancy. However, neither systemic nor central blockade of ANG II AT 1 receptors and of NO production, alone or together, improved the gain of arterial baroreflex control of renal sympathetic nerve activity or heart rate (27,41,48,149). These data suggest that a central action of ANG II and/or NO is not responsible for the decrease in baroreflex gain during pregnancy, at least via a rapidly reversible mechanism.…”
Section: Roles Of Ang II and No In Baroreflex Modulation During Pregnmentioning
confidence: 82%
“…Compared with nonpregnant animals, pregnant animals are more dependent on ANG II for maintenance of baseline arterial pressure (27,149). Moreover, acute administration of an AT 1 receptor antagonist, either intravenously or intracerebroventricularly, caused a leftward shift in both HR and RSNA baroreflex function curves, effectively reducing SNA at any given arterial pressure level (27,48,149). It has been suggested that the elevated baseline sympathetic activity in pregnant rats is a consequence of increased activity of PVN sympathoexcitatory neurons which in turn is due, at least in part, to the increased level of circulating ANG II that occurs (112) (Fig.…”
Section: Roles Of Ang II and No In Baroreflex Modulation During Pregnmentioning
confidence: 99%